数列求解
1个回答
展开全部
1)a1+2a2+...+2^n-1an=n/2(1)
a1+2a2+...+2^n-2a(n-1)=(n-1)/2(2)
(1)-(2)得2^(n-1)an=1/2
则an=1/2^n
2)bn=n*2^n
解:Sn=1×2^1+2×2^2+3×2^3、、、+(n-1)2^(n-1)+n2^n①
2Sn=1×2^2+2×2^3、、、、+(n-1)2^n+n×2^(n+1)②
①-②得得
-Sn=2+2^2+2^3、、、、、+2^n-n2^(n+1)
=2(1-2^n)/(1-2)-n2^(n+1)=2^(n+1)-2-n2^(n+1)=(1-n)2^(n+1)-2
∴Sn=(n-1)2^(n+1)+2
a1+2a2+...+2^n-2a(n-1)=(n-1)/2(2)
(1)-(2)得2^(n-1)an=1/2
则an=1/2^n
2)bn=n*2^n
解:Sn=1×2^1+2×2^2+3×2^3、、、+(n-1)2^(n-1)+n2^n①
2Sn=1×2^2+2×2^3、、、、+(n-1)2^n+n×2^(n+1)②
①-②得得
-Sn=2+2^2+2^3、、、、、+2^n-n2^(n+1)
=2(1-2^n)/(1-2)-n2^(n+1)=2^(n+1)-2-n2^(n+1)=(1-n)2^(n+1)-2
∴Sn=(n-1)2^(n+1)+2
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询